HISTOLOGICAL STUDY ON OPTIC TECTUM IN IRAQI WATER SNAKE TESSELATA TESSELATA (Baghdad Science Journal, 2025)
The ceiling of the midbrain has a couple of optic lobes which are prominent and used as an optic center that reflex what it receives from eye retina fibers. The histology of optic tectum has been studied in Iraqi water snake natrix tesselata tesselata . It was found that the number of optic tectum were seven main strata organized from the outside to the inside as follows : the stratum zonula (SZ), the stratum opticum (SO), the stratum fibrosum et griseum superficialis (SFGS), the stratum griseum central (SGC), the stratum album central (SAC), the stratum griseum periventricular (SGP), and the stratum album periventricular (SAP). the three last strata consider deep layers on the optic tectumIt was noticed that the thinnest strata was the first (SZ), which is (20-25)µ m, in its thickness, while the thickest strata was the third (SFGS), which is (150-180)µ m. this stratum consist of three substrata (a.b.c). it was found that the optic fibers that come from eye retina enter the optic tectum through the second stratum which is the (SO) . so these fibers go out from optic tectum through the sixth stratum which is the (AGP). the fourth (SGC) contained a concentrated cells of three types which are ,the medium pear shape neuron , medium fusiform neuron , and medium multipolar neuron.